Dampak Covid-19 terhadap kebijakan pajak pertambahan nilai (PPN) terbaru pada perekonomian Indonesia - Tyas, Ifadatul Laili Kusumaning; Putri, Dinsa Selia; Abdillah, Mohammad Rizky; Himmah, Nuzulia Faiqotul (Maliki Interdisciplinary Journal, 2024)
This journal aims to analyze the impact of the latest VAT policy on the Indonesian economy. The study uses a qualitative approach by conducting a literature review and theoretical analysis of the relationship between the impact of the latest VAT policy on the Indonesian economy. The main focus of this research is on which goods are affected by the latest VAT policy, including which goods are not directly affected by the implementation of this policy. The research results indicate that when the government implements the latest VAT policy, it leads to an increase in prices for some goods. However, this increase does not have a comprehensive impact on all existing goods.